Spectrum of Clinical and Radiological Presentation of Midgut Malrotation in Children and Adolescents: Case Series - Saurya Saurya; Poonam Sherwani; Garima Sharma; Sudhir Saxena (Thieme Medical and Scientific Publishers Pvt. Ltd., 2022)
Abstract Midgut malrotation is usually present in the early neonatal period with intestinal obstruction and bilious vomiting. However, sometimes it may present later in childhood and adolescence with atypical features and then may remain undiagnosed for long, adversely affecting the growth and development of the child. Here we describe three cases of intestinal malrotation with various atypical presentation and imaging findings.